Research on factors influencing tourists’ adoption of virtual reality technology based on VAM - Wang, Jinjin (International Journal of Innovative Research and Scientific Studies, 2024)
The present study utilizes the Value-based Adoption Model (VAM) to examine the determinants that influence the adoption of Virtual Reality (VR) technology for virtual tourism among domestic visitors. The focus is on perceived value, considering both benefits and costs. Data was collected from 238 visitors at a VR theme park. A questionnaire measured perceived value, benefits (novelty, visual appeal, usefulness), costs (expenses, discomfort, complexity), and hedonic motivation. Structural equation modeling was used to analyze the relationships between variables. Perceived novelty, visual appeal, and usefulness positively influence perceived value, while perceived discomfort and complexity negatively impact it. Hedonic motivation also has a positive influence. Perceived cost doesn’t significantly impact perceived value. To promote VR adoption in tourism, attractions should enhance perceived benefits (novelty, visual appeal, usefulness) and reduce perceived costs (discomfort, complexity). Interactivity and entertainment elements can enhance enjoyment and value. Visual content should be realistic and appealing. The comfort of VR devices is crucial, and complex usage should be avoided. Future research can explore gender and age differences and rural adoption intentions. This study contributes to the literature by providing insights into the factors driving VR adoption for virtual tourism. It underscores the role of perceived value and hedonic motivation in shaping consumers’ intentions to use VR technology for tourism experiences. Moreover, the findings offer practical guidance to marketers in promoting VR adoption within the tourism context.